Effect of Glucose Induction on Biofilm Density in Clinical Isolate Acinetobacter baumannii Patients in Intensive Care Unit of Dr. Soetomo Hospital, Surabaya - Lindarto, Wira W; Wasito, Eddy Bagus; Debora, Kartuti (Folia Medica Indonesiana, 2020)
This study aimed to analyze the effect of glucose induction on the clinical isolate biofilm density of Acinetobacter baumannii. Thirteen clinical isolates of A. baumannii non biofilm forming were collected from non-DM patients who were treated at the ICU of Dr. Soetomo Hospital, Surabaya, was treated with the addition of 0.08% glucose, 0.15% glucose, 0.2% glucose, and 0.4% glucose in TSB growth media, followed by biofilm density examination with Tissue Culture Plate Method (TCPM) using 96 wells flatbottomed polyesterene tissue culture plate and read by autoreader ELISA with a wavelength of 630 nm (OD630). Biofilm density obtained was analyzed using ANOVA statistical analysis. The results of OD630 showed that the biofilm density increased significantly at the addition of 0.2% and 0.4% glucose. There was a significant increase in biofilm density at the addition of 0.2% and 0.4% glucose so that the management of blood sugar levels in ICU patients was needed before and when medical devices were installed.